(untitled) (Bangladesh Journal of Medical Science, 2014)
Aim: Reciprocal translocation between retinoic acid receptor alpha (RAR?) gene on chromo- some 17 and promyelocytic leukemia (PML) gene on chromosome 15 is the hallmark for acute promyelocytic leukemia (APL). Three different PML/RAR? isoforms have been described; S-form, L-form and V-form. Our aims were to characterize the different types of PML/RAR? iso- forms in Malay patients with APL and to determine the outcome of these different types of iso-forms. Materials and methods: RT-PCR analysis was performed on 20 patients recruited from hematology-oncology ward. RT-PCR detected fusion transcript of PML/RAR? in all patients. Results and Discussion: Of these patients, 65% (13 patients) exhibited L/V-form, and 35% (7 patients) S-form. Total white blood cell count (TWBC) was higher in L/V-form (25 x 109/l) compared to S-form (2.1 x 109/l) (p < 0.05). Five years survival rate was 100% and 33.3% for L/V-forms and S-forms respectively (p<0.005). Conclusion: We conclude that L/V- forms is the commonest isoform among Malays. They presented at younger age with higher TWBC counts. Although the sample size is small, our preliminary data showed an interestingly longer survival outcome among L/V-forms compared to S-form. PML/RAR? isoforms could be used in future as risk stratification feature in patients diagnosed as APL. Further study with more number of patients is required. DOI: http://dx.doi.org/10.3329/bjms.v13i3.15553 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.311-315